Justin: teacher, philosopher and martyr - Sena Pera, Juan Pablo (Romanitas - Revista de Estudos Grecolatinos, 2016)
On this essay, we will present to the reader Justin Martyr, a II century Christian philosopher and theologian. To accomplish this task, we will give a brief summary of the use of the term διδάσκαλος in the Greek poetic and philosophical literature, in Flavius Josephus and the New Testament. Onwards, we will reconstruct the essential elements of Justin’s philosophical school at Rome. Aditionally, we will present Justin’s biographical data and a critical analysis of his legal procedure and conviction, as transmited by the Acta Iustini, Rescencion A. Finally, we will do a stylistic analysis of Justin’s Apology.